CLUSTER POLICY AS THE BASIS FOR IMPLEMENTATION OF INNOVATIVE PROCESSES IN RUSSIAN AND EUROPEAN PRACTICE - Inna Nikolaevna Akhunzhanova (Science and Innovation Center Publishing House, 2018)
The article studies the experience of successful development of innovative territorial clusters. It describes the experience of cluster policy implementation within the framework of innovative standards in European countries. The article indicates the best practices of the cluster policies in the following countries: the Belgium case shows the key importance of financing of selected cluster projects and the development of large innovative hubs; the Finland case, where the significant role belongs to the national and regional centers that are unions of business representatives, state and regional authorities, universities and institutes; the Hungary case, where cluster policies are a framework concept for the entire economic policy of the country. The article also analyzes the implementation of Russian cluster policy and reveals the similarities and differences regarding European cluster policies.